Sanitation risk factors contributing to diarrhea in children below five years in Igembe South Sub-County, Meru County, Kenya. - Anampiu, Jacob; Rutto, Jane; Kaimuri, MaryJoy; Kubai, Patrick (African Journal of Science, Technology and Social Sciences, 2024)
Introduction: Lack of safe water, poor hygiene, and poor sanitation account for about 90% of the diarrheal diseases in the world. Globally, half a million people lack adequate sanitation, leading to fatalities for over five million people annually. In Kenya, diarrhea still remains one of the top five causes of morbidity and mortality in children below 5 years. Aim: To identify the household sanitation risk factors contributing to diarrhea in under-five-year-old children in Igembe South Sub County in Meru County, Kenya. Study Design: A retrospective and cross-sectional study. Place and Duration of the study: Nyambene Sub-County Hospital, Igembe South Sub-County in Meru County, Kenya between December 2022 and March 2023. Methodology: The sample size was 196 children calculated from a population of 3,332 children who had diarrhea in Igembe South Sub County out of 22412 children who had diarrhea in Meru County for the last year. Data was analyzed by use of SPSS (2022) and ANOVA. Results: The study found a strong link (p=0.0034) between diarrhea cases in children under five and the absence of household latrines, as well as sanitation-related factors. It noted that many households lacked proper latrines, and many caregivers did not practice hand washing after handling child feces. Conclusion: The study identified access to safe drinking water as a key factor in reducing diarrhea in young children. The study recommends close monitoring of sanitation facilities and ongoing assessments of water source safety by the County Government of Meru and other stakeholders to improve overall hygiene and reduce diarrhea cases in the region.